2015
DOI: 10.1016/j.jpubeco.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Basic versus supplementary health insurance: Moral hazard and adverse selection

Abstract: This paper introduces a tractable model of health insurance with both moral hazard and adverse selection. We show that government sponsored universal basic insurance should cover treatments with the biggest adverse selection problems. Treatments not covered by basic insurance can be covered on the private supplementary insurance market. Surprisingly, the cost effectiveness of a treatment does not affect its priority to be covered by basic insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…A notable concern when estimating the effects of insurance on health outcomes is the potential presence of adverse selection and moral hazard. 16 In adverse selection health risky individuals would self-select into insurance, while moral hazard implies abuse of the medical scheme through over utilisation. 17 A classical method to evade the influence of these behaviours is randomly allocating the insurance amongst the subjects, which is not possible for secondary data based studies.…”
Section: Introductionmentioning
confidence: 99%
“…A notable concern when estimating the effects of insurance on health outcomes is the potential presence of adverse selection and moral hazard. 16 In adverse selection health risky individuals would self-select into insurance, while moral hazard implies abuse of the medical scheme through over utilisation. 17 A classical method to evade the influence of these behaviours is randomly allocating the insurance amongst the subjects, which is not possible for secondary data based studies.…”
Section: Introductionmentioning
confidence: 99%
“…It is needed for most households to get covered with that and in this regard, governmental organization should support households. Most of the studies confirmed the protective effect of supplementary insurance (27)(28)(29).…”
Section: Discussionmentioning
confidence: 69%
“…However, the finding is in contrast with another study which reported that health insurance has an effect on increased utilization of healthcare services, particularly in situations where an insured individual is still able to access quality care in the absence of insurance [ 33 ]. However, a notable concern with analysis of the influence of health insurance on care-seeking behaviour is the potential presence of a moral hazard that had been previously reported [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%